Identification and Characterization of Complex Glycosylated Peptides Presented by the MHC Class II Processing Pathway in Melanoma - Malaker, Stacy A. (J Proteome Res, 2016)
The MHC class II processing pathway presents peptides derived from exogenous or membrane-bound proteins to CD4+ T cells. Several studies have shown that glycopeptides are necessary to modulate CD4+ T cell recognition, though glycopeptide structures in these cases are generally unknown. Here we present a total of 93 glycopeptides from three melanoma cell lines and one matched EBV-transformed line, with most found only in the melanoma cell lines. The glycosylation we detected was diverse and comprised 17 different glycoforms. We then used molecular modeling to demonstrate that complex glycopeptides are capable of binding the MHC and may interact with complementarity determining regions. Finally, we present the first evidence of disulfide-bonded peptides presented by MHCII. This is the first large scale study to sequence glyco- and disulfide bonded MHCII peptides from the surface of cancer cells, and could represent a novel avenue of tumor activation and/or immunoevasion.